Diseño de la transición del protocolo Ipv4 hacia Ipv6 en la empresa grupo Játiva con base en consideraciones de seguridad en implementación de Ipv6 - Montaleza Paucar, Paúl Andrés (2022)
This degree project was conducted in the company Jativa group located in Codesa first stop in front of the military barracks in the city of Esmeraldas, where through the application of the survey it was identified that there are problems with the IPv4 protocol such as low performance in the transmission and security problems when sending data packets, In addition to the poor structuring of the existing network, on the other hand does not have its own network administration, these actions promoted that the company is vulnerable to attacks from third parties and depend on an external administration to manage its own network, which causes a greater investment of time and money, for this reason it generates the need to migrate from IPv4 to IPv6 in the company Grupo Jativa. Research methodologies were used for its realization, in order to make the problem known and identify the main needs. For the development of the project the following protocols were used: IPv6 addressing which allows us to know how it works, 568 is the standard for telecommunications cabling in commercial buildings, 569 allows the design for the adequacy of routes and channeling spaces, 606 provides the administration of the network infrastructure and 607 establishes the protection of telecommunication equipment. As a result, the migration from IPv4 to IPv6 was obtained in the company Grupo Jativa, highlighting the increase of packet transmission in 87% and a better data encryption thanks to the security protocols implemented in IPv6, optimizing favorably the resources such as data transmission time and the money that was invested in an external administration.